Wakil Gubernur dan Keistimewaan DIY - Bambang Purwoko; Wawan Mas'udi (Jurnal Ilmu Sosial dan Ilmu Politik, 2001)
The status of Yogyakarta as a special province has brought about a serious tension at both conceptual as well as practical levels. A close look at the process around the recruitment of the Vice Governor for this province shows that point. A new interpretation and design of Yogyakarta as a special province is demanded.